Sensitivity of Stock Returns Volatility and Money Market Rates: Insight from Nigeria - Aleke, Stephen Friday; Obidike, Paul C.; Okeke, Frankline C. S. A.; Echeonwu, Sandra Ijeoma; Emineke, Kalu O. (Department of Sharia Financial Management, Institut Agama Islam Negeri Sultan Amai Gorontalo, Indonesia, 2022)
The study focused on how money market factors affected the stock returnfluctuations in the Nigerian setting. The study specifically looked at the impact of Treasury bill rates and monetary policy rates on the return fluctuations in Nigeria from2002 - 2016 over the study period. Financial econometrics study was performed using descriptive statistics, unit root test, heteroscedasticity, autocorrelation, GARCH (1.1), and GARCH-X (1.1) models. The series' stationarity was confirmed using the PP test and the Equally Augmented Dickey-Fuller (ADF) test. Additionally, a Benchmark GARCH (1.1) model was estimated to study the volatility. A diagnostic test was run using the Ljung-Box Q-Statistics to determine the robustness of the calculated GARCH model. The overall finding indicated that there was significant volatility clustering that was still present in the Nigerian exchange group, suggesting that it would take some time for the market's reaction to volatility shocks from the prior period to be completely eliminated. The study also discovered that changes in treasury bill rates and monetary policy rates significantly reduce the volatility of returns on the stock in Nigeria, supporting the idea that there is an inverse link between the value of money and the value of capital markets.